PERAN PEMBELAJARAN PENCAK SILAT DALAM PEMBENTUKAN KARAKTER SISWA PADA MATA PELAJARAN PENDIDIKAN JASMANI DI SMP ISLAM ALAMIN CIKARANG UTARA - Takine Tathira; Rizki Aminudin; Ardawi Sumarno (Jurnal Porkes, 2026)
Learning pencak silat in physical education is not only aimed at developing students' physical abilities and self-defense skills but also plays an important role in character building. However, this potential does not always manifest automatically, as found in initial observations at SMP Islam Al-Amin Cikarang Utara which showed low levels of discipline, responsibility, cooperation, sportsmanship, and respect among students. This study aimed to examine the role of pencak silat learning in shaping these five character dimensions. A qualitative approach with an instrumental case study design was employed. Data were collected through non-participant observation over eight meetings, semi-structured interviews with the physical education teacher and principal, written group interviews with 31 students, and documentation. Data validity was ensured through source, technique, and time triangulation. The findings showed progressive character development among students. Discipline improved through adherence to consistently enforced training rules. Responsibility and cooperation developed through paired practice activities requiring coordination and mutual care. Sportsmanship and respect were fostered through consistent social interactions and teacher role modeling. In conclusion, pencak silat learning can serve as an effective medium for character formation when implemented in a planned, systematic, and continuous manner, supported by teacher consistency and school policies that favor character strengthening.